Climate justice: air quality and transitions from solid fuel heating - Magdalena Baborska-Narozny; Malgorzata Szulgowska-Zgrzywa; Martyna Mokrzecka; Agnieszka Chmielewska; Natalia Fidorow-Kaprawy; Ewelina Stefanowicz; Krzysztof Piechurski; Marta Laska (Buildings & Cities, 2020)
Of all the European Union’s member states, Poland has the most acute ambient air pollution problem. An urgent transition from solid-fuel heating ('e.g.' coal and wood) in the housing sector is required to improve air quality in the country. National regulations still allow the sale of solid fuels for heating, but some municipalities impose local resolutions with binding deadlines for solid-fuel bans. A real-world study covering 422 apartments in heritage tenements in Wrocław is presented. A link between domestic solid-fuel usage and tenure type is identified: solid fuels prevail in social housing. The transition to other forms of heating will adversely affect the inhabitants already vulnerable to fuel poverty. Solid fuel proves to be the least preferred heating option and is linked to substandard living conditions. Fuel poverty vulnerability for low-income households is established based on cost analysis for different heating options, thermal retrofit strategies, internal temperatures and apartment sizes. The results indicate that climate injustice is likely to occur for the poorest inhabitants due to their inability to afford increased costs. Policy implications to address this injustice are needed to ensure the transition from solid-fuel heating will avoid new vulnerabilities.   'Policy relevance' Domestic solid-fuel combustion for heating purposes is linked to poor air quality in urban areas in Poland. Heritage tenements are the most technically deprived building stock and their inhabitants are already vulnerable to fuel poverty. To improve air quality and respond to climate change, solid fuels need to be substituted with less polluting but more expensive heating options. Potential climate injustice (harm) is likely to occur if the poorest inhabitants cannot afford to heat their homes due to a ban on solid fuels. The change of heating needs to be combined with additional support (thermal retrofit and appropriate pricing of alternative fuels). Air quality-driven polices focused on solid-fuel eradication should not ignore fuel poverty already experienced mainly by social housing residents using expensive electric heating on a standard tariff. Fuel poverty has a gender aspect related to the gender pay gap that needs addressing.